Analisis Faktor-Faktor yang Mempengaruhi Permintaan dan Penawaran Buah Pisang di Provinsi Bali - MEDIARTANA, A.A. GEDE RAI; DEWI, RATNA KOMALA; AGUNG, I DEWA GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.1, Juli 2021, 2021)
Analysis of Factors Affecting the Demand and Supply of Bananas in the Province of Bali The need for bananas in Bali is very high and exceeds the production capacity of local farmers. In recent years many bananas have been imported from outside Bali. Discussing the issue of consumption and supply of bananas is inseparable from the factors that influence the demand and supply of bananas in the Province of Bali. The purpose of this study was to determine what factors influence the demand and supply of bananas in the Province of Bali. The study was conducted using secondary data time series per 2018-2009 period determined purposively. Data in this study was 40 time series data. The analytical method used is multiple regression test and classic assumption test with the help of SPSS 25 program. The results showed that the demand for bananas was simultaneously affected by the price of bananas, income per capita, and Hindu religious holidays. This is seen from the value of the F test, where F count (11.464) > F table (3.252) at ? = 5%. The price of bananas did not significantly affect the demand for bananas seen from the value of t-count (-1.849) > t-table (2.048), income per capita significantly affected the demand for bananas seen from the value of t-count (4.002) > t-table (2,048), Hindu religious holidays did not significantly affect the demand for bananas seen from the value of t-count (1.832) < t-table (2.028). The supply of bananas simultaneously is influenced by the price of bananas, the number of trees harvested, and the season. This is seen from the value of the F test, where F arithmetic (16.458) > F table (3.252) at ? = 5%. The price of bananas significantly affected the supply of bananas seen from the value of t-count (2.504) > t-table (2.028), the number of harvest trees significantly affected the supply of bananas seen from the value of t-count (6.188) > t-table (2,028), season did not significantly affect the supply of bananas seen from the value of t-count (0.237) < t-table (2.028).